Perancangan Koleksi Pakaian Remaja Wanita Ready to Wear Dengan Style Glam Rock pada Brand Ninos - Vecilia Agnes Wijaya; Soelistyowati - (Jurnal Vicidi, 2017)
This design was done to create a teenage girl fashion style from brand NINOS, that was inspired from glam rock music genre in the 70’s which shows teenage rebellion expression. From that point on, the writer was motivated to make a ready-to-wear fashion collection themed “Ribelle” which was destined as means for Indonesian teenage girl to express their emotion through their clothes that they wear.